AN EMERGENCY RESPONSE: THE AVAILABILITY OF ACCESS ROAD AT THE INTERNATIONAL AIRPORT - Ramadhan Dermawan; Heru Kusdarwanto; Minulya Eska Nugraha; Yudita Nirmala Kartikasari; Fadhilla Nina Rizkyanti (Journal of Airport Engineering Technology (JAET), 2023)
An access road is a road traveled by ARFF vehicles to connect the fire station with the runway or aircraft movement area. This research aims to identify the situation and opportunity of the access road built in Juwata Tarakan Airport to provide response time by rearranging aircraft movement management on the Main Apron and Taxiway. The research method used in this research is descriptive qualitative with gap analysis techniques and uses data collection through observation, interviews, and documentation. The result of this study can be used as a reference and guide in designing access roads under applicable regulations, and it is expected to complement and expand references in the development of science in the field of air transportation management. In addition, the position of the Fire Station is close to one of the Runways and is not in a strategic location (0°). So that we can achieve faster response time to the nearest Runway, the conclusion is that the Juwata Airport ARFF Unit cannot build an access road to national regulations because the Fire Station is directly opposite the old Apron and Taxiway. It is expected that Juwata Airport can make rearrangements related to aircraft movement management on the Main Apron and Taxiway.